Sierra Leone : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Requests for Waiver of Performance Criteria and Extension of Arrangement, and Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries. (IMF Staff Country Reports; Country Report ;, 2004)
This study focused on the medium-term objectives, the 2004 government budget, and other policies and measures for the program period. The preparation of a full Poverty Reduction Strategy Paper (PRSP) will play a crucial role in the process, as this would provide a road map for the government's medium-term efforts. Sierra Leone's poverty reduction efforts would be significantly assisted by a medium- to long-term framework to develop the mineral sector. The IMF staff discussed with the authorities ways to achieve the monetary targets under the program.